Types of the genus Exochus Gravenhorst, 1829 (Hymenoptera: Ichneumonidae: Metopiinae) deposited at the Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine - Varga, Oleksandr (Zootaxa, 2021)
The holotypes of the seventeen Palaearctic species of the genus Exochus described by Dr Valentyna Tolkanitz and stored at the Schmalhausen Institute of Zoology NAS of Ukraine (Kyiv) are revised. Diagnoses and illustrations for each species are provided.